Performance of Sisal Fabre as Natural Geotextile to Reinforce Soil Layers on Unpaved Road. - Kyomugasho, Lilian (Kabale University, 2024)
Natural geotextiles are strong synthetic fabric usually used in civil engineering construction projects such as high way that stabilizes loose soil. Geotextiles may be used to improve; the embankment stability against bearing capacity failure, stability against slope failure through the foundation, allow a more controlled construction over very soft or difficult foundation soils. And sisal fibre is the one of the most widely used natural fibre and is very easily cultivated. The soil sample was obtained from Nyamkana road in Ntungamo district and the laboratory tests were carried out at Mbarara Regional laboratory. The tests carried out included; field density compaction, maximum dry density and California bearing ratio. The main objective was to investigate the performance of sisal fibre as a natural geotextile to reinforce the soil layers on unpaved roads so that we solve the problem of developing potholes, rutting, corrugation, weak subgrade resulting into mud formation, poor drainage system, non-uniform narrow width, stoniness, and environmental pollution from dust during dry seasons, rapid gravel loss, and these all together have increased regular maintenance costs. The study was limited to some soil tests on subgrade materials, to achieve the objectives, the study undertook the following methodology, particle size distribution, atterberg’s limit, maximum dry density test and testing CBR in the laboratory. The findings relating to these laboratory tests include: The liquid limit was 38%, plastic limit was 21%, plasticity index 17%, MDD was increased from 1.829 to 1.849Mg/M3 and CBR values using 60,30 and 10 blows increased from 3.7% to 9.2%,6.9%, 5.2%after the application of sisal fibre after the second, third and fourth layers of the soil compared to the CBR values without sisal and particle size was obtained and the clay soil was classified as silty or clayey grave sand and soil sample fall under group classification of A-2-6. Finally, it was observed that placing sisal fibre after the second layer gives the highest CBR value and MDD values. Based on the results the expansive soil reinforced with sisal fibre at the second layer can be used in unpaved road layers since it gave an increase in CBR from 3.7% to 19.2% since it meets the requirement as per the Uganda ministry of works, Housing and communication, 2005 and the general specification for roads and Bridges. Further research should be conducted to assess the long-term performance of sisal fibres and its performance under different weather conditions